A Programmed DNA Marker Based on Bis(4‐ethynyl‐1, 8‐naphthalimide) and Three‐Methane‐Bridged Thiazole Orange. Issue 46 (29th September 2015) - Mao, Yueyuan; Liu, Keyin; Chen, Liang; Cao, Xinhua; Yi, Tao
Abstract: Two large conjugated naphthalimide derivatives with or without three‐methane‐bridged thiazole orange (TO3; i.e., compounds 1 a and 2 a, respectively) were designed and synthesized. The fluorescence of the naphthalimide group in compound 1 a at λ =532 nm initially decreased and that for the TO3 group at λ =655 nm increased sequentially upon adding Salmon testes (St) DNA. In contrast, without the TO3 group, the fluorescence intensity of compound 2 a monotonously decreased in response to the addition of DNA. The non‐monotonic change in the fluorescence for compound 1 a could be divided into two linear sections with two different wavelengths in the range of 0< R b/1 a <1.2 and 1.2 < R b/1 a <6.0 ( R b/1 a =[base pair]/[1 a ]). Thus, compound 1 a can be regarded as a programmed responding molecule for DNA, which can semi‐quantitatively determine the concentration of DNA over a large concentration range from the standard fluorescence curve of compound 1 a at different wavelengths when bound with DNA. Furthermore, the binding modes of compounds 1 a and 2 a with StDNA were studied by using CD spectroscopy and melting temperature ( T m ) testing. The results showed that compound 1 a interacts with StDNA through multi‐interactions including weak intercalation, weak minor groove binding, and inter‐dye interactions, whereas compound 2 a bound with DNA through simultaneous intercalation and minor groove binding. Abstract : Two for one : A naphthalimide derivative containing three‐methane‐bridged thiazole orange (TO3), which can selectively bind DNA in a programmed way that leads to a change in fluorescence, was designed and synthesized. The green emission at λ =532 nm (naphthalimide group; see figure) of the newly synthesized compound initially decreased and the red emission at λ =655 nm (TO3 group) increased sequentially with increased DNA concentration.